Media, Consumerism and the Environment: The Relationship of Media and Consumptive Behavior of Urban Society to Environmental Damage (MUHARRIK: Jurnal Dakwah dan Sosial, 2021)
In a few decades, the media has become the locomotive that controls the consumptive behavior of society, especially in urban areas. Massive media that aggressively offers easy access to meet all kinds of urban community needs encourages consumerism. The trend of consumerist urban lifestyle in the end must take consequences for environmental damage. As with Fast Food and Fashion which results in increased industrial production, the energy required for production is higher. At the same time, the energy used also comes from the exploitation of the earth. Scholars such as Jean Baudrillard suggest that people do not buy goods, but buy signs that ultimately symbolize themselves to confirm which group they belong to and belong to. To contribute to the existing studies, the study in this article aims to explore and analyze the relation of media to the consumptive behavior of urban society and its impact on environmental damage. By using the perspective of Jean Baudrillard, the media is the most significant contributor that encourages consumerism in urban communities so that it has an impact on environmental damage. The reality of the media has created a false consciousness so that consumer society only consumes signs, not goods and services. The emergence of visual waste impacts urban society's consumerism, resulting in the loss of public space and the strengthening of the greenhouse gas effect.